The more the better – polyandry and genetic similarity are positively linked to reproductive success in a natural population of terrestrial salamanders (Salamandra salamandra). Issue 1 (28th November 2013) - Caspers, Barbara A.; Krause, E. Tobias; Hendrix, Ralf; Kopp, Michael; Rupp, Oliver; Rosentreter, Katrin; Steinfartz, Sebastian
Abstract Although classically thought to be rare, female polyandry is widespread and may entail significant fitness benefits. If females store sperm over extended periods of time, the consequences of polyandry will depend on the pattern of sperm storage, and some of the potential benefits of polyandry can only be realized if sperm from different males is mixed. Our study aimed to determine patterns and consequences of polyandry in an amphibian species, the fire salamander, under fully natural conditions. Fire salamanders are ideal study objects, because mating, fertilization and larval deposition are temporally decoupled, females store sperm for several months, and larvae are deposited in the order of fertilization. Based on 18 microsatellite loci, we conducted paternity analysis of 24 female‐offspring arrays with, in total, over 600 larvae fertilized under complete natural conditions. More than one‐third of females were polyandrous and up to four males were found as sires. Our data clearly show that sperm from multiple males is mixed in the female's spermatheca. Nevertheless, paternity is biased, and the most successful male sires on average 70% of the larvae, suggesting a 'topping off' mechanism with first‐male precedence. Female reproductive success increased with the number of sires, most probably because multiple mating ensured high fertilization success. In contrast, offspring number was unaffected by female condition and genetic characteristics, but surprisingly, it increased with the degree of genetic relatedness between females and their sires. Sires of polyandrous females tended to be genetically similar to each other, indicating a role for active female choice.